Empirical Analysis of the Factors Influencing Employee Loyalty at PT BPR BKK Purwokerto - Lestari, Herwiek; Arinastuti, Arinastuti; Damayanti, Alfina; Pujiastuti, Ratna (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Employees, as vital assets, are essential for a company's effective operation, and neglecting their well-being can lead to substantial losses. A company's ability to prioritize employee welfare fosters a sense of loyalty, crucial for enhanced productivity. Employee loyalty, reflected in a desire to stay with a company, stems from a comfortable organizational environment. Factors influencing this loyalty encompass work motivation, discipline, leadership quality, and a positive non-physical work environment. This study at PT BPR BKK Purwokerto, utilizing multiple linear regression analysis on 60 respondents, reveals that work motivation, discipline, leadership, and the non-physical work environment significantly contribute to fostering employee loyalty. The implications of these findings underscore the strategic importance of holistic employee management in organizational success. By investing in motivational strategies, cultivating effective leadership, fostering disciplined work culture, and promoting a positive non-physical work environment, companies can create an environment conducive to lasting employee loyalty. This not only ensures employee satisfaction but also establishes a foundation for heightened productivity, reducing turnover costs and contributing to the long-term success of the organization.